Potency of Full- Length MGF to Induce Maximal Activation of the IGF-I R Is Similar to Recombinant Human IGF-I at High Equimolar Concentrations - Janssen, Joseph A. M. J. L.; Hofland, Leo J.; Strasburger, Christian J.; van den Dungen, Elisabeth S. R.; Thevis, Mario (PLOS ONE, 2016)
Aims To compare full-length mechano growth factor (full-length MGF) with human recombinant insulin-like growth factor-I (IGF-I) and human recombinant insulin (HI) in their ability to activate the human IGF-I receptor (IGF-IR), the human insulin receptor (IR-A) and the human insulin receptor-B (IR-B), respectively. In addition, we tested the stimulatory activity of human MGF and its stabilized analog Goldspink-MGF on the IGF-IR. Methods The effects of full-length MGF, IGF-I, human mechano growth factor (MGF), Goldspink-MGF and HI were compared using kinase specific receptor activation (KIRA) bioassays specific for IGF-I, IR-A or IR-B, respectively. These assays quantify activity by measuring auto-phosphorylation of the receptor upon ligand binding. Results IGF-IR: At high equimolar concentrations maximal IGF-IR stimulating effects generated by full-length MGF were similar to that of IGF-I (89-fold vs. 77-fold, respectively). However, EC50 values of IGF-I and full-length MGF for the IGF-I receptor were 0.86 nmol/L (95% CI 0.69–1.07) and 7.83 nmol/L (95% CI: 4.87–12.58), respectively. No IGF-IR activation was observed by human MGF and Goldspink-MGF, respectively. IR-A/IR-B: At high equimolar concentrations similar maximal IR-A stimulating effects were observed for full -length MGF and HI, but maximal IR-B stimulation achieved by full -length MGF was stronger than that by HI (292-fold vs. 98-fold). EC50 values of HI and full-length MGF for the IR-A were 1.13 nmol/L (95% CI 0.69–1.84) and 73.11 nmol/L (42.87–124.69), respectively; for IR-B these values were 1.28 nmol/L (95% CI 0.64–2.57) and 35.10 nmol/L (95% 17.52–70.33), respectively. Conclusions Full-length MGF directly stimulates the IGF-IR. Despite a higher EC50 concentration, at high equimolar concentrations full-length MGF showed a similar maximal potency to activate the IGF-IR as compared to IGF-I. Further research is needed to understand the actions of full-length MGF in vivo and to define the physiological relevance of our in vitro findings.